2012
DOI: 10.1080/00981389.2011.619860
|View full text |Cite
|
Sign up to set email alerts
|

The Writing Series Project: A Model for Supporting Social Work Clinicians in Health Settings to Disseminate Practice Knowledge

Abstract: Social work clinicians across health care settings are uniquely positioned to disseminate valuable practice experience, thereby contributing to knowledge development within their field of practice and across disciplines. Unfortunately, practitioners tend to shy away from writing and research, and are often reluctant to publicly disseminate their expertise through peer-reviewed journals and conference presentations. To better support health social workers in scholarly endeavors, we developed and implemented The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In busy workplaces writing can be seen as a luxury, one which may be imbued with feelings of guilt at taking 'time off' to write (Hislop, Murray and Newton, 2008). Other reported barriers, identified from a writing project in Australia, include lack of access to mentorship and training in writing skills (Boddy, Daly and Munch, 2012). Unfamiliarity with academic writing and publishing conventions have also been identified as challenges by practitioners who have seen their research through to publication (Staudt, Dulmus and Bennett., 2003).…”
Section: So Why Don't Social Workers Write For Publication?mentioning
confidence: 99%
See 3 more Smart Citations
“…In busy workplaces writing can be seen as a luxury, one which may be imbued with feelings of guilt at taking 'time off' to write (Hislop, Murray and Newton, 2008). Other reported barriers, identified from a writing project in Australia, include lack of access to mentorship and training in writing skills (Boddy, Daly and Munch, 2012). Unfamiliarity with academic writing and publishing conventions have also been identified as challenges by practitioners who have seen their research through to publication (Staudt, Dulmus and Bennett., 2003).…”
Section: So Why Don't Social Workers Write For Publication?mentioning
confidence: 99%
“…Boddy , Daly and Munch., 2012;Joubert, Epstein and Epstein, 2013;Smith, Wilkinson and Gallagher,2013). Doel (2002, 61) has suggested that this kind of alliance of practice and academy is potentially an extremely powerful one, bringing together 'people with something to say with people with experience of conveying ideas in writing'.…”
Section: Learning and Key Messagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitchell et al estimate that 'practitioner research in social work probably occupies a major part of the total volume of research activity in this (social work) field ' (2010, p. 8). This literature tends focus on the learning processes which enable practitioners to gain research skills and improve their individual capacity (Beddoe and Harrington, 2012;Boddy et al, 2012;McCrystal, 2000;Bond and Walton, 1998). Capacity development might include increased ability to produce peer-reviewed writing (Boddy et al, 2012), increased research confidence (Beddoe and Harrington, 2012) and research specific skills (Lunt and Fouche, 2009).…”
Section: Connecting Practitioner-research With Knowledge Mobilisationmentioning
confidence: 99%